Resilience to Discrimination Among Indigenous Sami and Non-Sami Populations in Norway: The SAMINOR2 Study. (August 2017) - Friborg, Oddgeir; Sørlie, Tore; Hansen, Ketil L.
Discrimination is generally negative for mental health and well-being; however, few studies have examined protective effects of resilience factors, especially among minority indigenous people. Here, we validated a short version of the Resilience Scale for Adults (RSA) and examined its protective effects against discrimination among Norwegian indigenous Sami and non-Sami populations. Data come from a large population-based survey of health and living conditions in multiethnic areas among indigenous Sami and non-Sami population (the SAMINOR2 study). The information was collected in 2012 from 11, 600 participants (18-69 years old). The main outcome measures were mental health (or distress) as measured with the Hopkins Symptom Check List (HSCL-10) and well-being as measured with the WHO-5 index by the World Health Organization. A 10-item short version of the original RSA (33 items) showed good model fit in all ethnic strata as well as factorial invariance, thus indicating cross-cultural validity. Being exposed to discrimination in general was more negative for the main outcome measures than exposure to ethnic discrimination alone; however, high scores on the RSA-10 almost canceled this negative effect completely. Minority participants with a strong Sami identity ( N = 1, 270) were least negatively influenced by discrimination, whereas majority ethnic Norwegians ( N = 5, 233) were most negatively affected. The strong Sami subgroup, thus, showed a remarkable resilience despite considerable exposure to discrimination. Members of this group were synergetically protected by individual ( personal strength ) and family ( cohesion ) resilience factors.